Mechanistic study of betulinic acid extraction from Tetracera scandens (L.) Merr. using bio-based solvents: molecular interactions, α-glucosidase docking, and solvent cytotoxicity - Le, Trong Nhan; Tran, The Huan; Nguyen, Hoai (Tạp chí Y Dược Huế, 2026)
Background: Betulinic acid (BA) is a poorly water-soluble triterpenoid, limiting its extraction efficiency from medicinal plants and motivating the use of bio-based solvents (BioSs). Objectives: This study aimed to elucidate the extraction mechanism of BA from Tetracera scandens using pentane-1,2-diol (PED) and hexane-1,2-diol (HED), to provide molecular-level insight into the potential interaction of BA with α-glucosidase using docking simulations, and to assess the cytotoxicity of the solvents. Materials and methods: Solvent–solute interactions were investigated using quantum chemical calculations. Molecular docking simulations with α-glucosidase were performed, and the cytotoxicity of the solvents was evaluated on HEK-293A cells. Results: PED and HED exhibited favorable interactions with BA, contributing to improved extraction efficiency. Molecular docking results indicated stable binding of BA to α-glucosidase. Both BioSs did not exhibit cytotoxic effects toward normal human cells. Conclusion: PED and HED are promising BioSs for the extraction of BA, and the proposed solvent system demonstrates appropriate mechanistic relevance and safety for potential applications.